2017
DOI: 10.1159/000480321
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Induces EMT in Bovine Mammary Epithelial Cells Through the TGFβ1/Smad Signaling Pathway

Abstract: Background/Aims: Transforming growth factor-β1 (TGF-β1) plays a crucial role in chronic inflammation in various tissues, and is related to inflammation-caused organ fibrogenesis associated with the epithelial-mesenchymal transition (EMT) and the deposition of the extracellular matrix (ECM). However, the effect of TGF-β1 on bovine mammary epithelial cells (BMECs) with mastitis, and its mechanism, remain unknown. Methods: We analyzed the level of TGF-β1 in inflamed mammary tissues and cells using western blottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 43 publications
3
56
0
1
Order By: Relevance
“…We have shown that TGF-b1 introduces EMT by the classical TGF-b1/Smad pathway in bovine mammary epithelial cells [20]. In this study, higher mRNA level ( Fig.…”
Section: Knockout Of Lncrna-tub Caused Lower Tuba1c and Higher Tgf-b1supporting
confidence: 59%
“…We have shown that TGF-b1 introduces EMT by the classical TGF-b1/Smad pathway in bovine mammary epithelial cells [20]. In this study, higher mRNA level ( Fig.…”
Section: Knockout Of Lncrna-tub Caused Lower Tuba1c and Higher Tgf-b1supporting
confidence: 59%
“…Studies have shown that EMT is closely related to invasion and migration in bladder cancer. 15 Thus, we further explored whether starvation-induced autophagy promoted EMT through the TGF-β/Smad signaling pathway. The epithelial marker E-cadherin was significantly expressed in the control group, CQ-only group, and 3MA-only group.…”
Section: Starvation-induced Autophagy Promotes the Invasion And Migmentioning
confidence: 99%
“…15 TGF-β1 is an extracellular membrane ligand that binds to the membrane-type TGF-β receptor II and activates TGF-β receptor I. TGF-β receptor I phosphorylates Smad2 and Smad3, further forming a complex with Smad4 and entering the nucleus to bind with other DNAbinding factors such as Snail, ZEB, and Twist to induce EMT. 15 TGF-β1 is an extracellular membrane ligand that binds to the membrane-type TGF-β receptor II and activates TGF-β receptor I. TGF-β receptor I phosphorylates Smad2 and Smad3, further forming a complex with Smad4 and entering the nucleus to bind with other DNAbinding factors such as Snail, ZEB, and Twist to induce EMT.…”
Section: F I G U R E 3 Autophagy Promotes the Invasion And Migration mentioning
confidence: 99%
See 1 more Smart Citation
“…TGFβ1 enhances bovine fibroblast proliferation through the MAPK/Erk pathway (Gao et al, 2016), and promotes the transition of fibroblasts to myofibroblasts (De Vries et al, 2011); the latter are key mediators of ECM protein synthesis and tissue fibrosis (Phan, 2008). Furthermore, TGFβ1 is known to cause bovine mammary epithelial cells to switch to a mesenchymal phenotype through a process known as epithelial-to-mesenchymal transition (EMT) (Chen et al, 2017). In bovine mammary epithelial cells, EMT was reported to occur (at least in part) through the Smad pathway (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%